1990
DOI: 10.1007/bf00197698
|View full text |Cite
|
Sign up to set email alerts
|

Infertility in human males with autosomal translocations: meiotic study of a 14;22 Robertsonian translocation

Abstract: Pachytene analysis was undertaken in a male patient heterozygous for a 14q22q Robertsonian translocation. The relatively low rate of XY autosome association led us to examine the relationships existing between the chromosomes involved in the translocation, the rate of XY-autosome association and the degree of spermatogenic failure. Cytogenetic investigations in infertile men and the results of the meiotic studies suggest a direct correlation between the frequency of XY-autosome association at pachytene and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
1
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 23 publications
3
35
1
4
Order By: Relevance
“…In addition, pairing of both chromosomes 13, initiated from telomeres, may also interfere with the formation of the XY body. 21,22 In the present study, an abnormal segregation of the (Y;13) was found during meiosis I, as only 13.6% of the secondary spermatocytes showed a normal chromosome complement. In this situation, most of the abnormal secondary spermatocytes might become arrested and degenerated, 18 which explains why the large majority of the round spermatids were normal (70%), as were in consequence most of the sperm (85.1%).…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…In addition, pairing of both chromosomes 13, initiated from telomeres, may also interfere with the formation of the XY body. 21,22 In the present study, an abnormal segregation of the (Y;13) was found during meiosis I, as only 13.6% of the secondary spermatocytes showed a normal chromosome complement. In this situation, most of the abnormal secondary spermatocytes might become arrested and degenerated, 18 which explains why the large majority of the round spermatids were normal (70%), as were in consequence most of the sperm (85.1%).…”
Section: Discussionsupporting
confidence: 48%
“…In the case of an X or Y/autosome translocation, a translocated chromosome will be included in the compartment of the XY body and inactivation may extend to the autosomal segment yielding degeneration of most spermatocytes after the pachytene stage. 21,22 The PAR1 (at XpYp) represents the region for sex-chromosome recombination and must be intact in order to promote meiotic pairing and ensure sperm production. 23 -25 However, the fact that the PAR 1 region is intact does not necessarily imply that the meiotic pairing is normal, as telomere TTAGGG repeats, rather than subtelomeric sequences, play an important role in meiotic pairing.…”
Section: Discussionmentioning
confidence: 99%
“…The t(14;22) and t(13;21) are two rare Rob translocations, the meiotic segregation pattern in spermatozoa only have two and one reports available in the literature by now, respectively [11,12,27]. Our data showed that alternate segregation was largely dominant over adjacent segregations in the two uncommon Rob translocations carriers (patient 5 and patient 6).…”
Section: Discussionmentioning
confidence: 51%
“…ROB is also one of the major chromosomal aberrations encountered in infertile men after numerical sex chromosome anomalies (Tuerlings et al 1998). This structural rearrangement has variable impacts on spermatogenesis, including germ cell depletion by reduction of spermatocyte I survival potential (Guichaoua et al 1990). …”
Section: Introductionmentioning
confidence: 99%